Methods of Humidityanalysis in Transformer Oil - Gutten, Miroslav; Kudelcik, Jozef (Communications - Scientific letters of the University of Zilina, 2010)
To prevent failure states of transformer, we performed different types of measurements. We made measurements of a frequency dependence of capacity of test transformer immersed in tank with transformer oil. The capacity illustrates a momentary state of the measured equipment and its variations to indicate the changes in the transformer oil. Water content in the transformer oil causes deterioration of its insulation and, finally, thermal defect of solid insulation.